(untitled) (Global Journal of Human-Social Science, 2024)
The COVID-19 pandemic has ushered in a new era of pedagogical strategies and offered a unique window into students’ lives. Among the many challenges and advantages of the online environment, the daily exposure to students’ lives-magnified during synchronous online teaching-served to humanize them in the classroom. This research delves into a novel area, exploring whether this heightened exposure to students’ day-to-day environments outside of the physical classroom leads to academic empathy from their instructors and whether it results in a better understanding of students’ individual challenges and circumstances. The results showed that synchronous instruction increased faculty members’ empathy for students’ diverse personal experiences. A significant discovery, however, was the role of student camera usage in enriching the synchronous online experience. Ultimately, the study underscores the benefits of students having cameras on during synchronous online classes to create a more connected and empathetic classroom environment.